Reframing test accommodation practice on English high-stake examination in Indonesia - Imam Khasbani (Universitas Islam Sultan Agung, 2019)
The need to provide equal education access through an inclusive system to students with difficulties (henceforth SwD) has witnessed a substantially growing interest in the last recent years. As a standard practice of education and accountability system is inseparable, the need to include SwD in large-scale assessments has also become a central interest of many pedagogical practitioners around the world. This situation has later initiated the invention of test accommodation. With their challenges and difficulties, SwD are not expected to take part in the regular procedure of assessments. This paper, with regard to the above assertions, seeks to examine the accommodation practice in Indonesian educational system. It will primarily focus on analysing the types of accommodation applied in the country’s English high-stake assessment and the evaluation of the effectiveness of the ongoing practice. Contrary to common belief, accommodation in a language test is not exclusively aimed to accommodate students with mobility and cognitive challenges. Test accommodation is also aimed at helping students who face difficulty in the language of classroom instructions. However, due to the limited space reason and the fact that the phenomenon of learning difficulties caused by the inability of students to understand the language of instruction is uncommonly reported in Indonesian educational settings, this paper will primarily focus on the accommodation issue for students with physical and mental difficulty. Apart from highlighting on the history of test accommodation as well as the related issues, this paper will cover the nature of Indonesia’s practice towards test accommodation and discuss its real implementation. Further recommendations on how the test accommodation should be conducted in Indonesia educational settings will be discussed.